Data analysis technique to extract threshold value for Fuzzy Inference System in classifying malicious agents - Musa N.A.; Yusoff M.Z.M.; Yusoff Y.; Ismail R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer forensics; Data handling; Fuzzy systems; Information analysis; Multi agent systems; Data analysis techniques; Domain experts; Fuzzy inference systems; Fuzzy threshold; Malicious agent; Threshold-value; Fuzzy inference